(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the disease pattern at the outpatient clinic of the High-Level Treatment Department, Traditional Medicine Hospital of the Ministry of Public Security from November 2022 to November 2024. Methods: A retrospective cross-sectional study was conducted on 13,000 medical records. Descriptive statistical analysis was performed using SPSS 22.0 based on ICD-10 classification and traditional medicine categories. Results: The majority of patients were male (86.4%), with a mean age of 66.1 ± 6.5. The disease pattern was mainly concentrated in circulatory system diseases (41.6%) and endocrine-metabolic diseases (40%). Hypertension (39.5%) and type 2 diabetes mellitus (30%) were the most common conditions. In traditional medicine, “vertigo syndrome” (40.2%) and “Xiao Ke” (31.6%) were the most prevalent patterns. Conclusion: The disease pattern is dominated by chronic non-communicable diseases in older adults, requiring long-term management and integrated treatment approaches combining modern medicine and traditional medicine.